Application of Zakat on Deposits in Bank: An Analytical Study Based on Islamic Law - Sadat, Anwar; Karimuddin, Karimuddin; Sagita , Fatri (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2024)
According to Islamic law, this article examines the concept of zakat on bank savings, focusing on how zakat is applied to savings. The objective is to provide a comprehensive overview of Islamic legal perspectives on zakat for savings and the interest earned from bank deposits. The goal is to clarify the requirements and conditions under which Zakat should be paid and to present a detailed analysis of these financial matters. The study employs the Ushul Fiqh methodology, utilizing comparative techniques through literature reviews and analyzing current societal trends. This approach allows for a thorough examination of both classical Islamic jurisprudence and contemporary interpretations. Data collection involved reviewing existing literature and observing societal phenomena to understand how Islamic law is applied to savings and interest in modern banking. The findings indicate that zakat must be paid on bank savings if they meet the criteria established in zakat regulations. Regarding interest earned on savings, the study notes that zakat should be paid according to the views of scholars who permit accepting interest. This comprehensive analysis provides valuable insights into the obligations of zakat on savings and interest, offering guidance for Muslims seeking to adhere to Islamic law in their financial practices.